Оптимістичний нігілізм - Ткаченко, М. А. (ХНУРЕ, 2023)
The philosophy of optimistic nihilism asserts that life has no inherent meaning, but this should not discourage individuals from enjoying their existence and creating their own purpose. The acceptance of the ultimate futility of life can free individuals from anxiety, as it emphasizes the insignificance of their problems in the grand scheme of things. Optimistic nihilism encourages individuals to focus on the present moment and appreciate the beauty and complexity of the world around them. The concept of optimistic nihilism challenges traditional religious and moral beliefs, suggesting that individuals should create their own moral codes based on reason and empathy. Optimistic nihilism does not advocate for a lack of responsibility or accountability, as individuals still have a responsibility to others and should strive to make the world a better place. While acknowledging the temporary nature of life, optimistic nihilism celebrates the wonder and uniqueness of individual experiences, emphasizing the value of enjoying life while it lasts.